THE IMPACTS OF ARTIFICIAL INTELLIGENCE DRIVEN INTERNET AND SOCIAL MEDIA ON BOOK READING HABITS: A CASE STUDY IN TWO INSTITUTIONS IN SOUTHERN DISTRICTS OF ODISHA - Bhanja, Pritish; Pranati Das; Sudarsan Sahoo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This work endeavours to find the impacts of Artificial Intelligence (AI) enhanced internet and artificial intelligence driven social media on book reading habits. The population chosen for this study is 97 students from two engineering colleges from Ganjam and Gajapati districts in Odisha. Basic information is collected through a questionnaire survey. The study tries to dive into finding that students are more inclined towards AI enhanced social media and less towards reading books. Therefore, the study tries to highlight the effect of AI driven social media on reading habits of engineering students. So, this work makes an effort to uncover the vulnerability of reading habits.